2016
DOI: 10.1038/nchembio.2249
|View full text |Cite
|
Sign up to set email alerts
|

A human microprotein that interacts with the mRNA decapping complex

Abstract: Proteomic detection of non-annotated microproteins indicates the translation of hundreds of small open reading frames in human cells, but whether these microproteins are functional is unknown. Here, we report the discovery and characterization of a 7-kilodalton human microprotein we named non-annotated P-body dissociating polypeptide (NoBody). NoBody interacts with mRNA decapping proteins, which remove the 5’ cap from mRNAs to promote 5’-3’ decay. Decapping proteins participate in mRNA turnover and nonsense me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
226
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(235 citation statements)
references
References 44 publications
7
226
0
2
Order By: Relevance
“…smORF regions are depleted of non-synonymous mutations and lack insertions and deletions, suggesting conservation at the peptide level 118,119 . Putative micropeptide-harbouring lincRNAs are expressed at higher levels and in a less restricted pattern than lincRNAs lacking smORFs 119 , implying that their translation or their peptide products may function more broadly than the transcription or transcripts of lincRNAs lacking smORFs.…”
Section: The Functions Of Lincrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…smORF regions are depleted of non-synonymous mutations and lack insertions and deletions, suggesting conservation at the peptide level 118,119 . Putative micropeptide-harbouring lincRNAs are expressed at higher levels and in a less restricted pattern than lincRNAs lacking smORFs 119 , implying that their translation or their peptide products may function more broadly than the transcription or transcripts of lincRNAs lacking smORFs.…”
Section: The Functions Of Lincrnasmentioning
confidence: 99%
“…DWORF is a human LOC100507537-encoded micropeptide that displaces SERCA-inhibitory peptides to increase sarcoplasmic reticulum calcium uptake and promote myocyte contractility 120 . The NoBody peptide is translated from the LINC01420 lincRNA and interacts with mRNA decapping proteins to control the number of 118 . SPAR is a peptide conserved between humans and mice and encoded by LINC00961, which inhibits mTORC1 activation and muscle regeneration 18 (FIG.…”
Section: The Functions Of Lincrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike these examples of larger proteins that are proteolytically processed to generate their biologically active small peptide products, micropeptides are translated directly from their precursor mRNA (Figure 2). A small number of well-studied micropeptides have indicated that these small proteins may act as important regulators in many fundamental events including development[25, 46, 7073], DNA repair[74], RNA decapping[29], calcium homeostasis[18, 19, 22, 24, 75]), metabolism[26], stress signaling[23], myoblast fusion[76] and cell death[68, 77]. However, given the putative large number of micropeptides, relatively little is known about their biological activities and regulation.…”
Section: Identification and Characterization Of Biologically Active Mmentioning
confidence: 99%
“…Functional proteomics has been successfully used by several groups to help identify interacting proteins of candidate micropeptides[23, 29]. By performing immunoprecipitations and mass spectrometry on the co-precipitated proteins, direct binding partners or components of a specific protein complex can be identified, which is strongly suggestive of the biological function of a micropeptide.…”
Section: Identification and Characterization Of Biologically Active Mmentioning
confidence: 99%